KARANTINA KESEHATAN DI DKI JAKARTA (SEBUAH TINJAUAN YURIDIS TERHADAP PERAN NEGARA TERHADAP PEMENUHAN KEBUTUHAN SAAT PEMBERLAKUAN PSBB) - Susetio, Wasis; Azis, Rizka Amelia; Nurhayani, Nurhayani (Universitas Esa Unggul, 2020)
To close the spread of the corona virus access, the Government of DKI Jakarta enforces health quarantine with a Large Scale Social Limitation (PSBB) pattern.Ã‚Â The word quarantine is regulated in the Law No. 6 Year 2018 concerning Health Quarantine in the form of house quarantine, regional quarantine, hospital quarantine or large-scale social restrictions by health quarantine officials.Ã‚Â The legal issues that can be identified are whether the determination of DKI Jakarta PSBB is in accordance with the laws and regulations and how the role of the government both the DKI Jakarta Provincial and the Central Government in fulfilling the provisions of Article 8 of Law No. 6 Year 2018.Ã‚Â This community service was carried out on April 2020 which includes licensing, preparing online invitations and compiling educational materials.Ã‚Â In the Law No. 12 Year 2011 concerning the formation of legislation in Indonesia, Provincial Regional Regulation is under the Government Regulations and Laws, as well as the Governor Regulation No. 33 Year 2002, must refer to and originate from the norms of the Regional Quarantine Law, and Government Regulation No. 21 Year 2020 concerning PSBB.Ã‚Â Reference to the Article 8 of Law No. 6 Year 2018, the central government is obliged to provide basic health services, food, and other daily necessities to everyone without discrimination, while the word Ã¢â‚¬Å“canÃ¢â‚¬Â based on the Article 21 paragraph (1) of the DKI Jakarta Governor Regulation No. 33 Year 2020 is in nature facultative or permissible (not mandatory).Ã‚Â Keywords: corona virus, health quarantine